Factoring Expressions
Factoring Expressions

Subtraction of Algebraic Expression

We at ask-math believe that educational material should be free for everyone. Please use the content of this website for in-depth understanding of the concepts. Additionally, we have created and posted videos on our youtube.

We also offer One to One / Group Tutoring sessions / Homework help for Mathematics from Grade 4th to 12th for algebra, geometry, trigonometry, pre-calculus, and calculus for US, UK, Europe, South east Asia and UAE students.

Affiliations with Schools & Educational institutions are also welcome.

Please reach out to us on [email protected] / Whatsapp +919998367796 / Skype id: anitagovilkar.abhijit

We will be happy to post videos as per your requirements also. Do write to us.

In Subtraction of Algebraic Expression from another,follow the following steps

1) Change the signs.

‘+’ ---> ‘- ‘

‘-‘ ----->’+’
of all the expressions which is to be subtracted and then the two expressions are added.
_______________________________________________________________________
2)Then add two expressions.

Example :

1) Subtract -7x from 5x

Solution :

= 5x – ( -7x)
=5x + 7x
= 12x
_______________________________________________________________________
2)x2 + y2 + 3xy from 4x2 + 2xy – 3y2

Solution :

=(4x2 + 2xy – 3y2) – (x2 + y2 + 3xy)
= 4x2 + 2xy – 3y2 - x2 - y2 - 3xy
=4x2 + 2xy – 3y2 - x2 – y2 - 3xy
= 3x2 - xy – 4y2
_______________________________________________________________________
3)What should be subtracted from a3 - 4a2 + 5a – 6 to obtain
a2 - 2a + 1 ?

Solution:

Let 'X' denote the required expression,
(a3 - 4a2 + 5a – 6) – X = a2 - 2a + 1
Hence , X = (a3 - 4a2 + 5a – 6) – (a2 - 2a + 1)
= a3 - 4a2 + 5a – 6 - a2 + 2a – 1
= a3 - 4a2 +5a – 6 - a2 +2a –1
= a3 - 5a2 + 7a – 7
_________________________________________________________________
4)Subtract a3 - 4a2 + 5a – 6 from the sum of 3a3 + a2 + 1 and a2 -2?

Solution:

= [(3a3 + a2 + 1) + a2 -2)] - (a3 - 4a2 + 5a – 6 )
= (3a3 + a2 + 1+ a2 -2) - (a3 - 4a2 + 5a – 6 )
= (3a3 + 2a2 -1) - (a3 - 4a2 + 5a – 6 )
= 3a3 + 2a2 -1 - a3 + 4a2 - 5a + 6
= 3a3 + 2a2 -1 - a3 + 4a2 - 5a + 6
= 2a3 + 6a2 - 5a + 5
Algebraic Expressions

Like and Unlike terms in Algebra
Addition of algebraic expressions
Subtraction of algebraic expressions
Multiplication of algebraic expressions
Division of algebraic expressions
Home Page